Effect of Gadolinium Doping on the Structure of Ce1-xGdxO2-x/2 Solid Solutions Prepared by Ionic Gelation Approach - Ilcheva, V.; Boev, V.; Lefterova, E.; Avdeev, G.; Dimitrov, O.; Bojanova, N.; Kolev, H.; Petkova, T. (Emerging Science Journal, 2024)
The current research aims to present the structural characterization of Gd-doped ceria powders and ceramics, investigating the structural evolution resulting from cerium substitution with Gd across the entire composition range from 0 to 100 mol.% Gd2O3. Ce1-xGdxO2-x/2 powders with varying Gd contents (0 ≤ x ≤ 1) were synthesized using the ionic gelation method followed by thermal annealing. The resulting powders were subjected to high-temperature treatment to obtain ceramics. Characterization methods included X-ray diffraction (XRD) to identify phase composition and confirm the formation of Ce1-xGdxO2-x/2 solid solutions, infrared spectroscopy (IR) and scanning electron microscopy (SEM) for structural and morphological studies, and X-ray photoelectron spectroscopy (XPS) to evaluate the electronic structure. Comparative analysis of Gd-doped calcined powders and sintered pellets revealed the impact of thermal treatment on the structural features of the resulting solid solutions, elucidating the influence of gadolinium substitution. The novelty of this research lies in demonstrating the successful preparation of Ce1-xGdxO2-x/2solid solutions via an alginate-mediated ion-exchange process and providing a detailed structural investigation over the entire range of dopant concentrations. This assessment highlights the feasibility for further research of these materials as suitable candidates for intermediate-temperature solid oxide fuel cells (IT-SOFCs) or catalyst applications. Doi: 10.28991/ESJ-2024-08-05-01 Full Text: PDF